PENGARUH PENDIDIDIKAN KESEHATAN AUDIOVISUAL TERHADAP PENGETAHUAN ORANG TUA MENCEGAH STUNTING PADA BALITA DI DESA MINAHASA UTARA - Bayu Dwisetyo (FKIP, Universitas Palangka Raya, 2021)
One of the main Stunting or dwarf is a condition when toddlers experience the failure of growth it caused by poor nutritional status of the children under five years. The Method of this study is to determine the effectiveness of audiovisual media on health education of parent's. The design of this study use a quasi-experimental (one group pre-test and post-test design). The population in this study found 112 parents. The samples taken 17 respondents by using purposive sampling. The research instrument is a questionnaire. Then the data collected and processed for analysis using the Mc Nemar test. The results of this study indicate, most of the poor knowledge of parents decreased after being given audiovisual media on health education. The results of data analysis using Mc Nemar test with p value = 0.000 (< 0.05), thus the alternative hypothesis (Ha) is accepted. The conclusion of this study is audiovisual media on health education on parental knowledge of preventing stunting in toddlers at Minaesa Minahasa. Suggestions to respondents, to seek more information about stunting prevention.